Phytochemical and Pharmacological Potential of Hygrophila spinosa T. Anders - Patra, Arjun; Jha, Shivesh; Murthy, P. Narasimha (Pharmacognosy Reviews)
Hygrophila spinosa T. Anders (Acanthaceae) is described in Ayurvedic literature as Ikshura, Ikshugandha and Kokilasha “having eyes like Kokila or Indian cuckoo”, common in moist places on the banks of tanks, ditches, paddy fields etc., widely distributed throughout India from Himalayas to Ceylon, Srilanka, Burma, Malaysia and Nepal. Seeds, whole plant, leaves, roots and ash of the plant are predominantly used for the treatment of various ailments. The compounds identified in H. spinosa are mainly phytosterols, fatty acids, minerals, polyphenols, proanthocyanins, mucilage, alkaloids, enzymes, amino acids, carbohydrates, hydrocarbons, flavonoids, terpenoids, vitamins and glycosides. Some of the reported phytoconstituents are lupeol, lupenone, 25-oxo-hentriacontanyl acetate, stigmasterol, betulin, β- carotene, hentriacontane, apigenin-7-O-glucuronide, apigenin-7-O-glucoside, 3-methylnonacosane, 23-ethylcholesta-11(12), 23(24)-dien-3β-ol, luteolin, asteracanthine, asteracanthicine, luteolin-7-rutinoside, methyl-8-n-hexyltetracosanoate, βsitosterol, histidine, phenylalanine, lysine, ascorbic acid, nicotinic acid, n-triacontane, glucose, mannose, rhamnose, arabinose, xylose, maltose, myristic acid, oleic acid, palmitic acid, stearic acid, linoleic acid etc. Ethanolic extract of the fruits, hydroalcoholic extract of whole plant and crude petroleum ether extract of the plant are having anticancer activity. Antibacterial activity was exhibited by the chloroform and methanol extract of the whole plant, and methanolic extract of the leaves. Antifungal activity against Aspergillus tamari, Rhizopus solani, Mucor mucedo and Aspergillus niger is due to the proteins and peptides present in the plant. Potential in treating liver diseases of the aerial parts, roots and whole plant was studied by various models viz. carbon tetrachloride induced hepatotoxicity, paracetamol and thioacetamide intoxication, and galactosamine induced liver dysfunction in rats. Seeds, leaves, aerial parts and roots showed antinociceptive activity which was studied using both chemical and thermal methods of nociception in mice. Some Ayurvedic, Unani and Siddha formulations of the plant are claimed to have anabolic-cum androgenic like activity. The plant was also studied for haematopoeitic, hypoglycemic, anti-inflammatory, antioxidant, hypotensive, diuretic, macrofilaricidal activities etc. Apart from the above established studies the plant is traditionally used for the treatment of anasaraca, diseases of urinogenital tract, dropsy of chronic Bright’s disease, hyperdipsia, vesical calculi, flatulence, diarrhea, dysentery, leucorrhoea, gonorrhoea, asthma, blood diseases, gastric diseases, painful micturition, menorrhagea etc. Therefore, these informations will help the scientists and researchers to screen the compounds responsible for different bioactivities and to elucidate the mechanism of action.
Keywords: Acanthaceae; Anticancer; Flavonoids; Hygrophila spinosa; Phytosterols